A dynamical artificial bee colony for vehicle routing problem with drones. (January 2022) - Lei, Deming; Cui, Zhengzhi; Li, Ming
Abstract: Truck-drone hybrid delivery is a hybrid one combining the advantages including large capacity of truck and high travel speed of drone together. Vehicle routing problem with drones (VRP-D) is a common one in the above delivery system. In this paper, VRP-D is addressed and a new dynamical artificial bee colony (DABC) is employed to minimize the overall operational cost. Two bee swarms are produced and an effective evaluation process is used to determine employed bee swarm and onlooker bee swarm dynamically. Variable neighborhood descent is constructed by using 15 neighborhood structures and adopted in employed bee phase and onlooker bee phase in different ways. A number of experiments are conducted on 112 instances and the computational results reveal that DABC provides new best solutions for 37 instances and has promising advantages on VRP-D.